Problematyka efektywności systemów zarządzania środowiskowego w obliczu konsolidacji przedsiębiorstw - Białowąs, Piotr (Problem of efficiency of environmental management systems in consolidation of enterprises, 2006)
The author of the article defines environmental management system and characterizes changes concerning consolidation companies. The article shows the influence of the changes connected with organization structure on environmental management system efficiency. The article presents the process of standardization of the criteria of checking environmental aspects in five companies and shows their influence on the policy of environmental protection.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 25-32